1963
DOI: 10.2466/pr0.1963.13.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Variations in Water Need and Incentive Concentration on Bar-Pressing

Abstract: 3 groups of 5 rats each were given daily bar-press training while 22.5 hr. water deprived. Each group always received the same reinforcement: 4%, 12%, or 36% sucrose. In counterbalanced order every S was given 5 different saline or water stomach loads, spaced at 1-wk. intervals. These were given an hour prior to regular training which followed as usual. Both water and saline loads depressed responding, and there was a significant interaction between loads and reinforcements. The only differential effect of suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1967
1967
1978
1978

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Many experiments have shown, however, that the water-deprived rat does not show this effect. It responds indiscriminately for water or different sucrose solutions in bar pressing situations (e_g., Beck, 1963;Collier, 1964;Oakley, 1965) until the sucrose reaches some high level of concentration (hypertonic) at which point it begins to prefer water over sucrose (Beck & Ellis, 1966). Indication that thirsty rats do prefer sucrose, however, comes from a study by Beck, Self, & Carter (1965) who found a higher sucrose preference threshold for waterdeprived (1_28%) than for non deprived (.43%) rats in 4-min tests, but nevertheless a preference.…”
Section: In Three Experiments It Was Demonmentioning
confidence: 99%
“…Many experiments have shown, however, that the water-deprived rat does not show this effect. It responds indiscriminately for water or different sucrose solutions in bar pressing situations (e_g., Beck, 1963;Collier, 1964;Oakley, 1965) until the sucrose reaches some high level of concentration (hypertonic) at which point it begins to prefer water over sucrose (Beck & Ellis, 1966). Indication that thirsty rats do prefer sucrose, however, comes from a study by Beck, Self, & Carter (1965) who found a higher sucrose preference threshold for waterdeprived (1_28%) than for non deprived (.43%) rats in 4-min tests, but nevertheless a preference.…”
Section: In Three Experiments It Was Demonmentioning
confidence: 99%
“…The non-deprived rat, food-deprived rat, and water-deprived rat after either drinking or stomach loading with water, bar-press for sucrose reinforcements ar races generally proportionzl to their concentrations (Guctman, 1953;Collier & Myers, 1959;Beck, 1963;McLean & Beck, 1964;Beck 8: Ellis, 1966). The thirsty rat, on the other hand, bar presses pretty much indiscriminately for water or different sucrose reinforcements (Beck, 1963;Beck 8: Ellis, 1966;Collier & Knarr, 1966;Oakley, 1965).…”
mentioning
confidence: 98%
“…Since each S received only a single stomach load, Hatton interpreted the depressive effect of NaCl as the result of a change in drive stimuli, conditioned drive stimuli having been replaced by the unconditioned stimuli evoked by the NaC1. Other investigators have reported depressive effects of NaCl loads which might be interpreted in the same manner (e.g., Beck, 1963;Beck & McLean, 1967).…”
Section: Wake Forest Universbymentioning
confidence: 92%
“…The apparatus, described more f~llly by Beck (1963), consisted of 3 identical Skinner boxes with automatic programming and recording. They were enclosed in ventilated ice chests in a room separate from the rest of the equipment.…”
Section: Subjectsmentioning
confidence: 99%